Psychomotricity and adversities in the teaching of early childhood education (Research, Society and Development, 2020)
Psychomotricity is one of the foundations in child development, a science that unites the body in movement and mental activity, admits a translation that relates body movement and its intentionality, studies human development in all phases. In this sense, this article aims to understand psychomotricity and adversities in early childhood education, to recognize the relationship between body and mind, and the importance of psychomotor development since childhood. In order to promote and achieve a deeper study on psychomotricity in early childhood education, this research took place in a bibliographic way through studies by authors dealing with the theme. The authors who guided this research were Duprê (1862-1921), Wallon (1879-1962) and Le Boulch (1981), who report the contexts and challenges of psychomotricity for a better development in human life. The results of the present study brought deeper reflections regarding the knowledge of the psychomotricity investigation process and the adversities in early childhood education.